Memanfaatkan NodeMCU dalam Serangan Jaringan Wi-Fi pada Frekuensi 2,4 GHz: Tinjauan Keamanan dan Tindakan Pencegahan - Wahyu, Gus Guswahyu; Kadyanan, Agung I Gusti Agung Gede Arya Kadyanan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2024)
NodeMCU, an open-source development platform based on the ESP8266, has become a significant tool in network security testing. This article investigates the use of NodeMCU in attacks against Wi-Fi networks on the 2.4 GHz frequency. We conducted experiments to launch NodeMCU's capabilities to exploit security weaknesses in Wi-Fi networks, including attacks against WEP, WPA, and WPA2 encryption. We also present preventive measures that can be implemented to protect Wi-Fi networks from attacks possible using NodeMCU.